Challenging Fabrication and Characterization of a New Ferroelectric Solid-Solution Composition 0.30Bi(Cu1/2Ti1/2)O3–0.70PbTiO3 - Prajapati K.; Khanuja S.S.; Singh A.K. (My University, 2025)
In this paper, an unexplored solid solution (1-x)Bi(Cu1/2Ti1/2)O3-(x)PbTiO3 has been synthesized and characterized for its crystal structure, dielectric and ferroelectric properties aimed at a selected composition, i.e., 0.30 Bi(Cu1/2Ti1/2)O3-0.70PbTiO3. The paper unveils the different synthesis approaches to achieve pure-phase in Pb-based perovskite-structured materials that are prone to produce impurities during synthesis. The Rietveld refinement of the XRD pattern confirms a tetragonal crystal structure (P4mm) of the composition. The ferroelectric properties of the as-prepared composition are also discussed using P-E hysteresis and PUND characteristics. The composition shows a high Tc (480 °C) and low dielectric losses, making it suitable for high-temperature applications. © 2023 Taylor & Francis Group, LLC.